On the effects of reducing the government's role in the labour market: a stylished model for Egypt with some numerical policy examples - Ole Risager; Chang-Po Yang (Copenhagen Business School (CBS), Department of Economics, 1999)
This paper analyzes the consequences of pursuing a less activist Government employment stabilization policy strategy in Egypt. On the basis of a fairly stylized model we find that a reduction of the Government's involvement in the economy along with an introduction of mild but binding firing regulations in the private sector may lead to a rise in total employment and to an improvement in Egypt's trade balance vis-à-vis the rest of the world.
hdl:10398/7659
Keywords: J40; 330; Uncertain environment; Job security; Countercyclical government intervention with lifetime employment guarantees; Wages; Employment; Labour market; Egypt